1996
DOI: 10.1117/12.235937
|View full text |Cite
|
Sign up to set email alerts
|

<title>Space object identification using spatiotemporal pattern recognition</title>

Abstract: This paper demonstrates the application of new pattern recognition techniques that can be used to characterize space objects. The feature space trajectory neural network (FST NN) was first presented by Leonard Neiberg and David P. Casasent in 1994 as a target identification tool. Kenneth H. Fielding and Dennis W. Ruck recently applied the hidden Markov model (HMM) classifier to a 3D moving light display identification problem and a target recognition problem, using time history information to improve classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As the aspect angle (0) changes, the feature point moves from O to 63°, then back to the center of the FST (for 0 = 900), then back to the 63° point for 9 = 900 + 27° = 117°, etc. Other work [11] has shown that FSTs give better P with fewer training set views and perform better in noise compared to aspect graphs using hidden Markov models. we showed that use of 11 aspect views over gives a negligible 3% difference in the values of each feature.…”
Section: Class and Pose Estimates Of 2 Similar Objectsmentioning
confidence: 97%
“…As the aspect angle (0) changes, the feature point moves from O to 63°, then back to the center of the FST (for 0 = 900), then back to the 63° point for 9 = 900 + 27° = 117°, etc. Other work [11] has shown that FSTs give better P with fewer training set views and perform better in noise compared to aspect graphs using hidden Markov models. we showed that use of 11 aspect views over gives a negligible 3% difference in the values of each feature.…”
Section: Class and Pose Estimates Of 2 Similar Objectsmentioning
confidence: 97%
“…In the case of socket 1 object in Fig. 1b, the section of the FST for views near 8 6 A is very close to the section of the FST for views around…”
Section: B Pose Estimationmentioning
confidence: 92%
“…There, the emphasis was on classification rather than pose estimation. Prior work showed that the FST gave superior performance compared to other classifiers [7,8], and overcomes problems that other classifiers have including: small training set size, ad hoc parameter selection, poor generalization, selecting the number of hidden layers, estimating distributions etc.…”
Section: Introductionmentioning
confidence: 99%